Begreppet Början. En begreppsstyrd undersökning av det svenska ordförrådets förändring under 500 år - Lange, Sven (Nordiske Studier i Leksikografi, 2010)
Every concept has a lexicon. How this lexicon changes over time is the main focus of this article. The concept of Beginning is investigated over a period of 500 years. All words in the lexical field, both the living and the obsolete ones, are represented in the study. A method consisting of several steps is presented to reach the “profile” of the concept and to grasp the interaction of first elements (i.e. prefixes and adverbs) and roots over time.